PENGEMBANGAN E-MODUL BERBASIS FLIPBOOK MATERI ASAL USUL NENEK MOYANG ORANG GORONTALO KELAS IV SD - Duawulu, Miqdad; Pulukadang, Wiwy Triyanty; Husain, Rusmin; Monoarfa, Fidyawati; Katili, Sukri (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study was motivated by the limitations of Indonesian language teaching materials in elementary schools, which are still conventional and do not optimize digital technology. The focus of this study is the low level of student engagement and motivation in learning local history narrative material because learning resources are limited to printed textbooks without interactive media variations. The purpose of this study is to develop a Flipbook-based E-Module on the Origin of the Gorontalo Ancestors for fourth-grade students at SDN 19 Limboto. The research method used was Research and Development (R&D) with the ADDIE development model, which includes five important stages: needs analysis, product design using Canva and Heyzine, product development through expert validation, implementation on 23 students, and final evaluation. Data collection instruments included validation sheets and response questionnaires for teachers and students. The results showed that expert validation of the material, language, and media gave an average score of 92.91%, which is categorized as “Very Suitable.” In the practicality test, 96.87% of teachers and 96.71% of students responded that it was “Very Practical.” The main conclusion of this study is that the Flipbook-based E-Module on the Origin of the Gorontalo Ancestors has been tested for feasibility and practicality, making it highly relevant for use as an innovative learning medium to improve the quality of literacy based on local wisdom in elementary schools. ABSTRAK Penelitian ini dilatarbelakangi oleh keterbatasan bahan ajar Bahasa Indonesia di sekolah dasar yang masih bersifat konvensional dan belum mengoptimalkan teknologi digital. Fokus masalah dalam penelitian ini adalah rendahnya keterlibatan dan motivasi belajar siswa pada materi narasi sejarah lokal karena sumber belajar yang hanya terpaku pada buku teks cetak tanpa variasi media interaktif. Tujuan penelitian ini adalah mengembangkan E-Modul berbasis Flipbook pada materi Asal Usul Nenek Moyang Orang Gorontalo untuk siswa kelas IV SDN 19 Limboto. Metode penelitian yang digunakan adalah Research and Development (R&D) dengan model pengembangan ADDIE yang meliputi lima tahapan penting: analisis kebutuhan, perancangan produk menggunakan Canva dan Heyzine, pengembangan produk melalui validasi ahli, implementasi pada 23 siswa, serta evaluasi akhir. Instrumen pengumpulan data meliputi lembar validasi serta angket respon guru dan siswa. Hasil penelitian menunjukkan bahwa validasi ahli materi, bahasa dan media memberikan nilai rata-rata 92,91% dengan kategori